Analisis Karakteristik Campuran Aspal Beton Ac-Bc (Asphal Concrete – Binder Course) Dengan Penggunaan Abu Kulit Kopi Sebagai Filler - Yanto, Agus Budi (Jurnal Proyek Teknik Sipil, 2025)
The objective of this research is to evaluate the characteristics of Asphalt Concrete–Binder Course (AC-BC) mixtures by utilizing coffee husk ash as a filler material. Coffee husk is an organic waste byproduct from the coffee bean processing industry, which has rarely been used in the construction sector. This study was conducted with variations of coffee husk ash filler proportions of 25%, 50%, 75%, and 100% of the total filler, and applied the Marshall test method to analyze stability, flow, VMA, VIM, VFA, and the Marshall Quotient. The test results indicated an Optimum Asphalt Content (OAC) of 5.25%. Mixtures with 25% and 50% filler content demonstrated performance that met the 2018 Bina Marga specifications, with good values of stability, VFA, and MQ, while the 75% and 100% variations showed a decline in quality. Coffee husk ash has potential as a substitute filler in AC-BC asphalt mixtures; however, its use is recommended not to exceed 50% in order to maintain the quality and performance of the mixture. The findings of this study serve as a reference for developing more environmentally friendly and cost-effective pavement materials.